Cloud Backup Management with PowerHA SystemMirror - Quintero, Dino; Chandolu, Umamaheswara; Sree, Aruna; Gee, Kevin; Kurapati, Sandhya; Yalamuri, Vijay (IBM Redbooks, 2021)
This IBM® Redpaper chapterexplains how to take a backup of your data by using either of two methods, and it explains how to recover your data if there is a disaster. This paper addresses topics for IT architects, IT specialists, developers, sellers, and anyone looking to implement and manage backups in the cloud. Moreover, this publication provides documentation to transfer the how-to-skills to the technical teams and solution guidance to the sales team. This book complements the documentation that is available at IBM Documentation and aligns with the educational materials that are provided by IBM Garage"!for Systems Technical Education
Online resource; Title from title page (viewed September 14, 2021)